Vertical Integration of Chicken Egg Prices in Central Java (An Error Correction Model (ECM) Analysis) - Nurul Khotimah; Mochammad Yunus Gerry Fitriadi; Rizky Lutfi Suprabowo (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2026)
Despite high production levels, chicken egg prices in Central Java experience significant volatility. This study analyzes the degree of vertical price integration and identifies the price leadership structure among producers, wholesalers, and retailers in the chicken egg market in Central Java Province. While previous research has examined market integration, a gap remains in understanding price leadership dynamics amid recent post-pandemic economic shifts. This study addresses this gap by providing empirical evidence of vertical price transmission using updated time-series data (2021–2024) across producer, wholesaler, and retailer levels. The ECM approach was employed, with data stationarity first verified via the Augmented Dickey-Fuller (ADF) test. Price leadership was then identified through a two-step analysis of short-term regression and the error correction term. The ADF results indicate that the chicken egg market in Central Java is vertically integrated in both the short- and long-run. The ECM result demonstrates that price adjustments originate at the producer and wholesaler levels and are transmitted forward to retailers in both the short and long run (p < 0.05), confirming a supply-led price leadership structure. These findings contribute to the literature by clarifying that upstream segments dictate price formation in the regional market. Consequently, policymakers should prioritize stabilization efforts at the producer level, particularly through feed-cost subsidies and wholesale distribution management, to effectively mitigate volatility across the value chain.